(untitled) (Journal of Environmental Microbiology and Toxicology, 2017)
Today, numerous researches have demonstrated the cost-effectiveness of bioremediation to waste removal from agricultural and industrial sectors particularly at lower levels of the toxicants, where other physicochemical techniques are ineffective. Multiple toxicant remediation by a single microorganism is important for remediation of sites contaminated with numerous toxicants. In this work, a molybdenum-reducing bacterium was screened for its ability to use the xenobiotic polyethylene glycol (PEG) as the sole source of carbon for growth and as electron donor source for molybdate reduction. Biochemical analysis results in the tentative identification of the isolate as Enterobacter cloacae strain KIK-14. The use of PEGs as an electron donor in this bacterium did not support molybdenum-blue production, even though the bacterium grew well on PEGs 200, 300, 600 and 1000 independent of molybdate reduction. Reduction of molybdate to Mo-blue was optimal at pH between 6.0 and 6.3, the temperature between 25 and 37 oC, molybdate and phosphate concentrations between 15 and 20 mM and between 5.0 and 7.5 mM respectively. The best electron donor source supporting the reduction process was glucose. The Mo-blue absorption spectrum resembles reduced phosphomolybdate and is similar to that of the previous Mo-reducing bacterium. At 2 ppm of silver, mercury and copper, molybdenum reduction was inhibited by 41.5, 57.1 and 40.5%, respectively. The ability of this bacterium to detoxify mixed toxicants makes it an important tool for bioremediation.